Impact of Alcohol Abuse on Susceptibility to Rare Neurodegenerative Diseases - Araujo, Iskra; Henriksen, Amy; Gamsby, Joshua; Gulick, Danielle (Frontiers in Molecular Biosciences, 2021)
Despite the prevalence and well-recognized adverse effects of prenatal alcohol exposure and alcohol use disorder in the causation of numerous diseases, their potential roles in the etiology of neurodegenerative diseases remain poorly characterized. This is especially true of the rare neurodegenerative diseases, for which small population sizes make it difficult to conduct broad studies of specific etiological factors. Nonetheless, alcohol has potent and long-lasting effects on neurodegenerative substrates, at both the cellular and systems levels. This review highlights the general effects of alcohol in the brain that contribute to neurodegeneration across diseases, and then focuses on specific diseases in which alcohol exposure is likely to play a major role. These specific diseases include dementias (alcohol-induced, frontotemporal, and Korsakoff syndrome), ataxias (cerebellar and frontal), and Niemann-Pick disease (primarily a Type B variant and Type C). We conclude that there is ample evidence to support a role of alcohol abuse in the etiology of these diseases, but more work is needed to identify the primary mechanisms of alcohol’s effects.